(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Any uterine bleeding outside the normal volume, duration, regularity or frequency is considered as abnormal uterine bleeding (AUB). Nearly thirty percent of all gynaecological outpatient attendants are for AUB. Abnormal menstrual bleeding pattern have been traditionally expressed by terms like menorrhagia, metrorrhagia, polymenorrhagia & oligomenorrhoea. Normal menstrual cycle interval is 28 days (21-35 days), menstrual flow duration 4-5 days and normal menstrual blood loss should be 35ml (20-80 ml). Any deviation in the above criteria comes under abnormal uterine bleeding, means excessive amount of bleeding or increased duration of bleeding during menstruation or both termed as AUB. In Ayurveda same is described as Pradara. A female patient aged 22 years visited OPD of Prasuti Tantra and Stri Roga department of NIA, with complaints of heavy menstrual bleeding and prolonged menstrual bleeding more than seven days since six months. Pictorial blood loss assessment chart was used to assess the amount of blood loss before and after treatment. SF-36 questionnaire was assessed to know the improvement in quality of life. Patient was given Kutajashtakaleha 10 gm BD with cows milk.